China's compliance in global affairs : trade, arms control, environmental protection, human rights - Chan, Gerald (Series on contemporary China, 2006)
The rise of China has thrown open many important and interesting questions: Will a strong China behave responsibly in world affairs, complying with the rules and norms of the?international community?? Or will it defy?universal standards?, and fight instead for its own interests and those of the developing world, thereby challenging the global order dominated by the West? The first of its kind to gauge in a comprehensive manner China's responsibility in world affairs, this book scrutinizes China's compliance with international rules and norms, embodied in the treaties that it has signed or ratified, especially in the areas of trade, arms control and non- proliferation, protection of the environment, and human rights. The book also examines Sino-US relations, as the US closely monitors China's compliance in world affairs. It is that behavior which is largely determining the relative emphasis put on engagement with or containment of China by the West, and by the US in particular.